Reframing Representation and Visibility in Modern Exhibition Spaces through Innovative Curatorial Practices and Artistic Interventions - Akintayo Ezekiel Akintobi (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This paper explores the evolving paradigms of representation and visibility in contemporary exhibition spaces, emphasizing the transformative potential of innovative curatorial practices and artistic interventions. Traditional exhibition models have often been critiqued for reinforcing dominant cultural narratives and marginalizing alternative perspectives. In response, a new generation of curators and artists is reimagining exhibition methodologies to foster inclusivity, pluralism, and participatory engagement. Drawing on case studies from diverse cultural contexts, the study examines how spatial design, digital integration, and collaborative programming can be leveraged to amplify underrepresented voices and challenge established hierarchies of visibility. The research underscores the curatorial shift from static, object-centered displays to dynamic, audience-centered experiences that encourage critical dialogue and co-creation. It also highlights the role of interdisciplinary strategies merging visual arts, performance, sound, and interactive media in constructing narratives that reflect complex socio-political realities. By adopting reflexive curatorial frameworks, institutions are negotiating tensions between aesthetic innovation and socio-political accountability, ensuring that exhibitions not only present art but also act as catalysts for cultural discourse and social change. The paper argues that such approaches demand a reconfiguration of institutional roles, with curators functioning as mediators, facilitators, and advocates for equity. Furthermore, the integration of digital platforms expands the reach of exhibitions beyond physical boundaries, enabling global participation and fostering transnational dialogues on identity, memory, and belonging. This reframing of representation is not merely a formal or stylistic shift but a critical intervention that challenges exclusionary systems and promotes cultural resilience. Ultimately, the study concludes that innovative curatorial practices, when combined with artist-led interventions, have the capacity to transform exhibition spaces into sites of active cultural negotiation, fostering visibility for diverse communities and redefining the relationship between art, audience, and institution.